Analisis Bisnis BMT Dana Mentari Muhammadiyah Purwokerto dengan Menggunakan Matriks McKinsey - Amatuloh, Zahwa Nabilla; Dameiyanti, Titis; Nuraini, Septia Intan; Shafrani, Yoiz Shohwa (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the business position of BMT Dana Mentari Muhammadiyah Purwokerto using the McKinsey Matrix as a strategic analysis tool. The method used is a qualitative approach with data collection through literature studies, observations, and interviews with BMT managers. The data obtained were analyzed using the McKinsey Matrix to assess market attractiveness and business strength in each business unit. The study results indicate that most of the BMT Dana Mentari Muhammadiyah Purwokerto business units are in the blue and yellow zones in the McKinsey Matrix, indicating the need for selective development and maintenance strategies. This analysis also recommends effective and efficient resource allocation to improve the competitiveness and performance of BMT in the Islamic microfinance market. Thus, the use of the McKinsey Matrix has been proven to help BMT in determining the priority of business strategies that are adaptive to market dynamics and competition.